A review of the damselfly genus Megalestes Selys, 1862 (Insecta: Odonata: Zygoptera: Synlestidae) using integrative taxonomic methods - Yu, Xin; Xue, Junli (Zootaxa, 2020)
We used morphological and molecular characters to review the classification of damselflies in the genus Megalestes Selys, 1862 (Zygoptera: Odonata). Several methods were used for this review, including morphology, cladistics, genetic distance analysis, and molecular taxonomy. Six species were newly defined as junior synonyms (Megalestes palaceus to Megalestes haui, Megalestes chengi to Megalestes micans, Megalestes discus to Megalestes micans, Megalestes raychoudhurii to M. micans, Megalestes maai to Megalestes riccii, and Megalestes tuska to M. riccii). The total species number in Megalestes was reduced from 18 to 12. The importance of an objective species diversity measure is discussed.